Antibody and T cell responses to COVID-19 vaccination in patients receiving anticancer therapies. Issue 6 (22nd June 2022) - Rouhani, Sherin Juliet; Yu, Jovian; Olson, Daniel; Zha, Yuanyuan; Pezeshk, Apameh; Cabanov, Alexandra; Pyzer, Athalia R; Trujillo, Jonathan; Derman, Benjamin A; O'Donnell, Peter; Jakubowiak, Andrzej; Kindler, Hedy L; et al.
Abstract : Background: Patients with cancer were excluded from phase 3 COVID-19 vaccine trials, and the immunogenicity and side effect profiles of these vaccines in this population is not well understood. Patients with cancer can be immunocompromised from chemotherapy, corticosteroids, or the cancer itself, which may affect cellular and/or humoral responses to vaccination. PD-1 is expressed on T effector cells, T follicular helper cells and B cells, leading us to hypothesize that anti-PD-1 immunotherapies may augment antibody or T cell generation after vaccination. Methods: Antibodies to the SARS-CoV-2 receptor binding domain (RBD) and spike protein were assessed in patients with cancer (n=118) and healthy donors (HD, n=22) after 1, 2 or 3 mRNA vaccine doses. CD4 + and CD8 + T cell reactivity to wild-type (WT) or B.1.617.2 (delta) spike peptides was measured by intracellular cytokine staining. Results: Oncology patients without prior COVID-19 infections receiving immunotherapy (n=36), chemotherapy (n=15), chemoimmunotherapy (n=6), endocrine or targeted therapies (n=6) and those not on active treatment (n=26) had similar RBD and Spike IgG antibody titers to HDs after two vaccinations. Contrary to our hypothesis, PD-1 blockade did not augment antibody titers or T cell responses. Patients receiving B-cell directed therapies (n=14) including anti-CD20 antibodies and multiple myeloma therapies had decreased antibody titers, and 9/14 of these patients were seronegative for RBD antibodies. No differences were observed in WT spike-reactive CD4 + and CD8 + T cell generation between treatment groups. 11/13 evaluable patients seronegative for RBD had a detectable WT spike-reactive CD4 + T cell response. T cells cross-reactive against the B.1.617.2 variant spike peptides were detected in 31/59 participants. Two patients with prior immune checkpoint inhibitor-related adrenal insufficiency had symptomatic hypoadrenalism after vaccination. Conclusions: COVID-19 vaccinations are safe and immunogenic in patients with solid tumors, who developed similar antibody and T cell responses compared with HDs. Patients on B-cell directed therapies may fail to generate RBD antibodies after vaccination and should be considered for prophylactic antibody treatments. Many seronegative patients do develop a T cell response, which may have an anti-viral effect. Patients with pre-existing adrenal insufficiency may need to take stress dose steroids during vaccination to avoid adrenal crisis.